2014
DOI: 10.4236/jbise.2014.78056
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of EEG to the Diagnosis of Dementia

Abstract: Changes induced by cerebrovascular damage (CVD) and amigdalo-hippocampal atrophy (AHC) on brain rhythmicity as revelaled by scalp electroencephalography (EEG) were evaluated in a cohort of subjects with mild cognitive impairment (MCI) in order to detect different EEG patterns due to the vascular or degenerative impairment. All subjects underwent EEG recording and magnetic resonance imaging (MRI). EEGs were recorded at rest. Relative power was separately computed for delta, theta, alpha1, alpha2, and alpha 3 fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 88 publications
1
2
0
Order By: Relevance
“…The correlation between PDDM95 and MMSE was highest at channels F7 (r(24) = -.77, p = 3.5x10 -6 )and lowest at channel O2 (r(24) = -.66, p = 2.7x10 -4 ). These results are consistent with previous reports [30,36,64,65] reporting the correlation between EEG measures and MMSE scores in AD. However, there was no significant correlation between EEG measures and MMSE scores in the MCI group.…”
Section: Plos Onesupporting
confidence: 93%
“…The correlation between PDDM95 and MMSE was highest at channels F7 (r(24) = -.77, p = 3.5x10 -6 )and lowest at channel O2 (r(24) = -.66, p = 2.7x10 -4 ). These results are consistent with previous reports [30,36,64,65] reporting the correlation between EEG measures and MMSE scores in AD. However, there was no significant correlation between EEG measures and MMSE scores in the MCI group.…”
Section: Plos Onesupporting
confidence: 93%
“…Several authors have reported increments in the EEG spectral power at slower frequencies (delta and theta) and a decrease in alpha band energy, especially in alpha-1, in individuals with Alzheimer's disease (AD), vascular dementia and mild cognitive impairment (MCI) [21,[34][35][36]. In particular, higher power in the theta band over the temporal lobe compared to agematched control has been proposed as a marker of Alzheimer's dementia [37].…”
Section: Plos Onementioning
confidence: 99%
“…Several authors have reported increments in the EEG spectral power at slower frequencies (delta and theta) and a decrease in alpha band energy, especially in alpha-1, in individuals with Alzheimer's disease (AD), vascular dementia and mild cognitive impairment (MCI) [21,[34][35][36]. In particular, higher power in the theta band over the temporal lobe compared to agematched control has been proposed as a marker of Alzheimer's dementia [37].…”
Section: Plos Onementioning
confidence: 99%